IDENTIFICATION OF VEGETATION STRESS USING SENTINEL 2 SATELLITE IMAGES IN KAMOJANG GEOTHERMAL FIELD AND SURROUNDING AREA - Muhammad Akrom, Fadhil
The Guntur-Kamojang Volcano Complex is a series of active volcanoes that have a geothermal system below the surface. It is characterized by the presence of manifestations on the surface and thermal anomalies in the area. The Kamojang Geothermal Field was chosen as the research location because it is the oldest geothermal field in Indonesia with high steam temperatures. In order to identify the geothermal system at the research site, a remote sensing approach and geological observation are carried out. This study aims to identify the geothermal system from vegetation stress data using Sentinel 2 satellite images and geological observations. The methods used in this research include analysis of vegetation index based on remote sensing techniques in high temperature geothermal areas, physical analysis of plants, and chlorophyll values of plant leaves. The results of the extraction of the vegetation index were then correlated with the field vegetation stress data using a linear regression equation. Vegetation stress anomalies related to the geothermal fluid outflow zone were identified in five locations, the first being the location of the manifestation in the Pangkalan area, the second in the Kamojang Crater area, the third in the Masigit Crater and Mount Gandapura, the fourth location in the Guntur Mountain crater, and the fifth location is in the southern part of Kamojang. The vegetation stress anomaly in the Kamojang, Masigit, Paruhpuyan and Guntur areas is an upflow zone of hydrothermal fluid output to the surface. Meanwhile, Pangkalan and South Kamojang areas are indicated as secondary anomalies that are not directly related to surface manifestations.